2010
DOI: 10.1038/jid.2010.196
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Pattern Recognition Receptors in Normal and Inflamed Human Epidermis: Upregulation of Dectin-1 in Psoriasis

Abstract: Human epidermis plays an important role in host defense by acting as a physical barrier and signaling interface between the environment and the immune system. Pattern recognition receptors (PRRs) are crucial to maintain homeostasis and provide protection during infection, but are also causally involved in monogenic auto-inflammatory diseases. This study aimed to investigate the epidermal expression of PRRs and several associated host defense molecules in healthy human skin, psoriasis, and atopic dermatitis (AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 62 publications
5
50
0
Order By: Relevance
“…In contrast, gal-8 and gal-9 expression was similar in all three types of sample ( Fig 1A). Dectin-1 was detected at high level in lesional skin, in agreement with a recent report [17].…”
Section: Galectin Expression Is Defective In Psoriatic Skinsupporting
confidence: 92%
“…In contrast, gal-8 and gal-9 expression was similar in all three types of sample ( Fig 1A). Dectin-1 was detected at high level in lesional skin, in agreement with a recent report [17].…”
Section: Galectin Expression Is Defective In Psoriatic Skinsupporting
confidence: 92%
“…Several groups investigated PRR expression in psoriatic lesions. Lesional TLR2 mRNA and protein expression levels are similar to those in normal skin [15,16], although two older studies suggested differently [17,18]. Transforming growth factor alpha, which is induced in psoriasis, was shown to increase TLR5 and TLR9 expression and function in keratinocytes.…”
Section: Prrs As Villains In Primary Skin Disordersmentioning
confidence: 90%
“…Also, TLR2, TLR3 and TLR4 ligands were shown to induce the psoriasis-associated cytokine TNF-α in human keratinocytes [18]. It is, however, controversial whether TLR4 is expressed in primary human keratinocytes, because several authors did not find TLR4 expression or effects of lipopolysaccharide (LPS) stimulation in these cells [15,20]. …”
Section: Prrs As Villains In Primary Skin Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in the mycobiome occurring in the absence of classical infections have been implicated in a wide range of diseases, such as chronic hepatitis B virus (HBV) hepatitis (25), atopic dermatitis (71), dandruff (72), IBD (73)(74)(75), cystic fibrosis (24), allergy/atopy (64), asthma (76), and psoriasis (77,78). There is no obvious pattern of fungal alterations in these diseases; pathology can be associated with either a decreased or increased diversity from that seen in the healthy state.…”
Section: The Mycobiome In Health and Diseasementioning
confidence: 99%